UMPSA organises AI Generation Festival 2025 (AIGenFest2025) to spark digital transformation through generative artificial intelligence - Naqiah, Puaad (UMPSA, 2025)
CYBERJAYA, 25 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), through the Centre of Excellence for Advanced Industrial Technology in collaboration with Gig Venture, successfully organised the AI Generation Festival (AIGenFest2025) on 24 and 25 May 2025 at Rekascape, Cyberjaya.